PERAN MASJID PARIPURNA DALAM PEMBINAAN UMAT (STUDI DI MASJID PARIPURNA AL-MUJAHIDIN KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU) - Supriyanto "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted in the Mosque complete Al-Mujahidin District Payung Sekaki City’s Pekanbaru with the aim to know the form of public participation (jama’ah) and the role of the Mosque complete Al-Mujahidin in the development of or society. What ate the form of public participation (jama’ah) then how the role Mosque complete Al-Mujahidin in realizing function Masque as the development of or society. This study using research kualitatif thedescriptive. The subject in this study amounts to 8 people with 3 people as e key informants and 5 as informants. In the data collection researchers use a technique observations, the interview, and the documentation. Analysis result of thedescriptive analysis suggests that in public participation om each activities or the show is not much different with Mosque in general in the city of Pekanbaru by gives the program invited jama’ah or society. This is where we can see the shape of the participation of society among them is to present in the tablig akbar, the day of Islam, filling Ramadhan, the study routine dawn every Saturday and Sunday as well as giving aid to the public good form to moral and material. The results of observasi researchers shows the role of given Mosque as the development of or society is to give the container education religion for the community, as Mosque pilot for other Mosque, and container coaching youth and teenagers as well as a forum to improve the walfare of society. Keywords: The role of Mosque Session, Coaching People.